2019
DOI: 10.13057/biodiv/d201020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of culture filtrate from Trichoderma spp. as biofungicide to Colletotrichum gloeosporioides causing anthracnose disease in chili

Abstract: Abstract. Nurbailis, Djamaan A, Rahma H, Liswarni Y. 2019. Potential of culture filtrate from Trichoderma spp. as biofungicide to Colletotrichum gloeosporioides causing anthracnose disease in chili. Biodiversitas 20: 2915-2920. Trichoderma spp. have the potential to be used for controlling the airborne pathogenic fungi such as C. gloeosporioides. The purpose of this study was to evaluate the antifungal activity of the culture filtrate of five isolates of Trichoderma spp. (T. harzianum, T. viride, T. koningii, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In another study, the CFs of various Trichoderma species, including T. harzianum (29.88 mm ) and T. viride (27.13 mm ), demonstrated remarkable suppression of R. oryzae ( Alka and Prajapati, 2017 ). Additionally, the CFs of five Trichoderma species ( T. viride, Trichoderma PP3, T. harzianum , Trichoderma PP2, and T. koningii ) as biofungicides exhibited strong hindrance to C. gloesporioides growth ( Nurbailis et al., 2019 ). Various studies have reported the significant mycelial growth inhibition of various fungal pathogens ( Filizola et al., 2019 ; Mulatu et al., 2022 ), which sturdily confers the biocontrol potential of Trichoderma CFs, and these evidently support the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, the CFs of various Trichoderma species, including T. harzianum (29.88 mm ) and T. viride (27.13 mm ), demonstrated remarkable suppression of R. oryzae ( Alka and Prajapati, 2017 ). Additionally, the CFs of five Trichoderma species ( T. viride, Trichoderma PP3, T. harzianum , Trichoderma PP2, and T. koningii ) as biofungicides exhibited strong hindrance to C. gloesporioides growth ( Nurbailis et al., 2019 ). Various studies have reported the significant mycelial growth inhibition of various fungal pathogens ( Filizola et al., 2019 ; Mulatu et al., 2022 ), which sturdily confers the biocontrol potential of Trichoderma CFs, and these evidently support the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…represent a significant in vitro and in vivo reduction of a fungal pathogen, Rhizopus oryzae , causing Rhizopus rot of tomatoes ( Alka and Prajapati, 2017 ), when culture filtrates of Trichoderma species were applied. Additionally, the culture filtrates of various Trichoderma species as biofungicides against various fungal pathogens, viz., Colletotrichum gloeosporioides ( Nurbailis et al., 2019 ), against anthracnose of great millet ( Manzar et al., 2021 ), Pythium species, and Phytophthora species, demonstrated inordinate antifungal potential ( Ben M'henni et al., 2022 ). The use of various Trichoderma species has widely been reported as an eco-friendly and safe approach to the control of plant diseases ( Alka and Prajapati, 2017 ; Nurbailis et al., 2019 ; Manzar et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study by Alka et al represent a significant in vitro and in vivo reduction of a fungal pathogen, Rhizopus oryzae, causing Rhizopus rot of tomatoes (Alka and Prajapati, 2017), when culture filtrates of Trichoderma species were applied. Additionally, the culture filtrates of various Trichoderma species as biofungicides against various fungal pathogens, viz., Colletotrichum gloeosporioides (Nurbailis et al, 2019), against anthracnose of great millet (Manzar et al, 2021), Pythium species, and Phytophthora species, demonstrated inordinate antifungal potential (Ben M'henni et al, 2022). The use of various Trichoderma species has widely been reported as an eco-friendly and safe approach to the control of plant diseases (Alka and Prajapati, 2017;Nurbailis et al, 2019;Manzar et al, 2022).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Additionally, the culture filtrates of various Trichoderma species as biofungicides against various fungal pathogens, viz., Colletotrichum gloeosporioides (Nurbailis et al, 2019), against anthracnose of great millet (Manzar et al, 2021), Pythium species, and Phytophthora species, demonstrated inordinate antifungal potential (Ben M'henni et al, 2022). The use of various Trichoderma species has widely been reported as an eco-friendly and safe approach to the control of plant diseases (Alka and Prajapati, 2017;Nurbailis et al, 2019;Manzar et al, 2022). The application of culture filtrates (CFs) of Trichoderma species as biocontrol not only acts as biostimulants against the inhibition of pathogens but also induces systemic or localized resistance in plants to biotic stresses and, ultimately, as a growth regulator, increases plant biomass (Abbas et al, 2019;Guzmań-Guzmań et al, 2019).…”
Section: Data Availability Statementmentioning
confidence: 99%